Possibilities for more effective use of trenchless rehabilitation techniques of sewage pipes - Kuliczkowska, Emilia; Kuliczkowski, Andrzej (Instal, 2021)
Based on the 30 years of experience of the Kielce University of Technology in the field of testing and assessing the technical condition of sewage pipes, some measures have been proposed to extend the service life of pipes and thus less frequent use of trenchless rehabilitation techniques. A literature study of selected methods of more effective than before using trenchless techniques is also presented